How Do Teachers Appropriate Learning Objects Through Critical Experiences? A Study of a Pilot In-School Collaborative Video Learning Lab - Lussi Borer, Valérie; Ria, Luc; Durand, Marc; Muller, Alain (Form@re - Open Journal per la formazione in rete, 2014)
This two-year longitudinal study examined the collective and individual effects of a collaborative video learning lab (CVLL) in a French lower-secondary high-poverty school. The CVLL was designed to: i) determine the learning objects shared by the in-service teachers based on their actual teaching activities and ii) encourage them to participate in a collaborative inquiry on their filmed activity regarding the selected shared learning object, with the goal of supporting them as they appropriate more efficient teaching practices..The participants were novice in-service teachers (n=2) and experienced teacher-facilitators (n=2). Data consisted of cross-analysis of video recordings (n=37) from i) classroom teaching activity (n=11), ii) CVLL sessions (n=6), and iii) teachers’ observations and comments on both (n=20). The results revealed that novice and experienced teachers lived critical experiences in the CVLL regarding the shared learning object and show how they transformed their activity as teachers, mentors or facilitators. Questo studio longitudinale di due anni esamina gli effetti collettivi e individuali di un laboratorio di apprendimento collaborativo con video (CVLL) in una scuola secondaria inferiore francese con alto grado di povertà. Il CVLL è stato progettato per: i) determinare i learning object condivisi dai docenti in servizio in base alle loro reali attività di insegnamento e ii) incoraggiarli a partecipare ad un’indagine collaborativa sulle attività videoregistrate concernenti il learning object condiviso selezionato, con l’obiettivo di sostenerli nel fare proprie pratiche di insegnamento più efficaci. I partecipanti sono insegnanti novizi in servizio (n=2) e insegnanti facilitatori esperti (n=2). I dati raccolti consistono in un’analisi incrociata delle registrazioni video (n=37), da i) attività didattica in aula (n=11), ii) sessioni CVLL (n=6), iii) osservazioni e commenti degli insegnanti su entrambi (n=20). I risultati mostrano che gli insegnanti hanno vissuto esperienze significative nel CVLL per quanto riguarda il learning object condiviso e che essi hanno trasformato la loro attività come insegnanti, mentori o facilitatori.